Penegakan Hukum Bagi Pelaku Pembuatan Dan Penyebaran Scam page (Studi Di Kepolisian Daerah Jawa Timur) - Radya Dzuhrizha Rahmana; Adhitya Widya Kartika (Jurnal Risalah Hukum, 2022)
In this thesis research, the author uses the empirical juridical method, meaning a research that has achievements in finding theories about the law enforcement process for community crimes. This research also aims to see and understand law enforcement for the perpetrators of creating and spreading scams. The data sources of this research were obtained from interviews with IPTU Niken Charisma Lahardi, S.E. as Investigator of the Sub Directorate V of the Cyber ??Crime Unit of the East Java Regional Police and data were obtained from the Sub Directorate V of the East Java Regional Police of the Cyber ??Crime Unit, legislation, and literature. The results of this study concluded that the perpetrators of creating and spreading scampages in 2021 were 1 case with 2 suspects. Law enforcement carried out by the Sub-Directorate V of the Ditreskrimsus Cyber ??Unit of the East Java Regional Police is based on and takes into account the elements of law enforcement, namely legal certainty, legal benefits and legal justice. In law enforcement, there are factors that influence it, namely in the form of law enforcement officials, legal factors, community factors, facilities and facilities factors and also legal culture factors. Based on the analysis that the author carried out in law enforcement carried out by the East Java Regional Police using the theory put forward by Joseph Goldstein, which is very relevant is the theory of actual law enforcement or actual enforcement because the theory is actual law enforcement which has limitations in it. Law enforcement according to Lawrence M. Freidmanm's theory, the Regional Police of East Java is based on legal culture.